HUBUNGAN AKTIVITAS BERMAIN LOMPAT TALI DENGAN KEMAMPUAN MOTORIKKASAR ANAK USIA DINI(Penelitian di Kelompok B RA Al-Wafi Bumi Panyileukan Bandung) - Nurhalimah Nurhalimah; Teti Ratnasih (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research is motivated by the results of preliminary observations in group B RA Al- Wafi Bumi Panyileukan Bandung, namely the existence of an interesting phenomenon from the activity of playing jumping rope how enthusiastic children are and also enthusiasm but on the other hand children are also not able to play well. So that there is a gap between the high activity of playing jumping rope and the low gross motor skills of some children. This study uses a quantitative approach and correlation method. The subjects in the implementation of this study were group B children of RA Al-Wafi Bumi Panyileukan Bandung, totaling 15 children. Academic Year 2019/2020. Data collection techniques in this study through observation and documentation. The results of data analysis on the variable Jumping play activity (Variable X) obtained an average value of 0.28 The value is in the interval 0-49 with a sufficient category. While the data analysis on the gross motor ability variable (Variable Y) obtained an average value of 0.75. This value is in the 70-79 interval with a good category. The results of the significance test obtained the price ????ℎ???????????????????? = 1.26> ???????????????????????? = 1771 That is, Ha is accepted and Ho is rejected in other words, there is a positive and significant relationship between jumping rope play activities and children's emotional intelligence in group B RA Al- Wafi Bumi Panyileukan Bandung. The coefficient of determination or the level of influence is 44% Thus, 57% of children's emotional intelligence in group B1 RA Al-Wafi Bumi Panyileukan Bandung, is influenced by other factors.